Converting Biomass to Energy : A Guide for Developers and Investors - International Finance Corporation (Washington, DC, 2017)
Biomass resources are found almost everywhere and can become a reliable and renewable local energy source to replace fossil fuels. Energy produced from biomass can reduce reliance on an overloaded electricity grid and can replace expensive fuels used in local industries. The International Finance Corporation (IFC) presents this guide as a practical tool to help developers of and investors in biomass projects assess the technical and financial feasibility of the different biomass-to-energy options available to their businesses and industries. This guide describes all the necessary steps in the development of a biomass-to-energy project. Following this introductory chapter, the authors present an overview of the entire project development process, so that project developers have an idea of the overall process they are about to enter. Next, the guide describes biomass resources and how to secure biomass supply. This is followed by several in-depth chapters covering the technology aspects, plant design, plant procurement, construction, and operation. After the more technical aspects, the guide focus on framework conditions, investment costs, financial and economic analysis, and securing financing. Finally, the guide presents potential environmental and social considerations and concludes with a chapter on the lessons learned from implemented biomass-to-energy projects.